Effect of carbon nanotube surface treatment on the dynamic mechanical properties of a hybrid carbon/epoxy composite laminate. (5th January 2023) - Brown, Avery D.; Bakis, Charles E.; Smith, Edward C.
Abstract: The objective of the current investigation is to evaluate the dynamic mechanical properties of a hybrid carbon fiber reinforced epoxy composite laminate containing CNT-rich interlayers, where the CNTs were prepared with ten different surface treatments and two different degrees of alignment. The surface treatments, including surfactants and oxidation, alter the CNT/epoxy stress transfer characteristics. Testing was done in uniaxial tension at different temperatures, loading frequencies and in dry and wet conditions. In the case of imperfectly aligned CNT yarn interlayers, the best surfactant, which was Triton X-100, increased the loss modulus by 182% over the baseline (no CNTs) and increased the storage modulus by 2.2%. Oxidation of the CNTs increased the loss modulus by 219% and the storage modulus by 2.3%, versus the baseline. Highly aligned CNT film provides higher loss modulus (+44%) and storage modulus (+8.4%) than imperfectly aligned CNT yarns, for the case of no surface treatment. Alignment of the CNTs also reduces the sensitivity of dynamic properties to temperature change and moisture content. CNT interlayers reduce the frequency dependency of the dynamic properties. Improvements in damping with surface treatments are hypothesized to be due to improved epoxy impregnation of the condensed CNTs. Graphical abstract: Image 1 Highlights: Carbon fiber epoxy composites are manufactured with carbon nanotube interlayers. Surface-treated nanotubes can increase damping over untreated nanotubes. Oxidizing nanotubes increases damping without decreasing the glass transition temperature. Aligning nanotubes increases damping and decreases sensitivity to temperature and moisture. Nanotubes reduce the dependence of dynamic properties on loading frequency.